Proyecto de desarrollo agro-industrial del cultivo de la yuca en la Costa Atlantica de Colombia (agosto 1987-julio 1988). Informe Anual [online] - Ostertag Gálvez, Carlos F. (International Center for Tropical Agriculture, 1988)
The activities of the agroindustrial development project conducted by CIAT on the northern coast of Colombia, from August 1987 to July 1988, included elaboration of dried cassava chips for animal nutrition, production and marketing of bagged cassava, milling and mixture of dried cassava, survey of cassava drying plants, var. improvement and selection, agronomy, and CF production and marketing for human consumption. The fresh cassava conservation project has promoted the creation of 4 cooperatives competent in this technology. The product has a greater price stability than traditional fresh cassava. Milling and mixing CF for animal feed will reduce transportation costs of dried cassava for distant markets and will promote the local manufacture of concentrates to reduce the cost of animal feeds. The follow-up of dried cassava projects has allowed the social impact of the project to be assessed. On-farm evaluation of local var. has identified the different end markets for cassava as well as local cultural practices; var. of maize/yam for intercropping have been identified in agronomic trials and improved production technology has been compared with traditional technology. The accelerated multiplication of planting material has also begun. Plans for 1989 include the establishment of a CF pilot plant. (CIAT)